Detection of Malicious Intrusion Using R Based Random Forest Algorithm in Machine Learning - R, Vinotha; P, Seethamani. (International Journal of Psychosocial Rehabilitation, 2020)
The need to secure networks has increased as the number of people connecting to the network is increasing rapidly and using networks for storing or accessing critical information. An assessed and compared various machine learning algorithms and then proposed a system based on the best-performing algorithm. A system is an intrusion prediction system with a low error rate that can be implemented in the real world. The dataset utilized in the project comprises a lot of information to assess, remembering an assortment of reproduced intrusions for a military system condition. The dataset contains mainly the normal state, DDoS, and some other attacks. The system will not only predict a malicious network but will also indicate exactly what type of attack the network is on.